Ecosystem Service Supply in the Antarctic Peninsula Region: Evaluating an Expert-Based Assessment Approach and a Novel Seascape Data Model - Neumann, Barbara; Mikoleit, Anton; Bowman, Jeff S.; Ducklow, Hugh W.; Müller, Felix (Frontiers in Environmental Science, 2019)
The Southern Ocean and coastal Antarctica provide a variety of ecosystem services with benefits for humankind that are of regional and global importance. Despite being nearly uninhabited, increasing exploitation of natural resources, a growing human presence, and environmental change threaten the sustained provisioning of these services. Ecosystem service assessments have proven as a suitable tool to understand the relevance of ecosystems for human well-being and guide decision-making, but the fluid and transboundary nature of marine ecosystems poses challenges to analyzing ecosystem services in regions with large marine sections. New methods to objectively assess the supply of ecosystem services for such realms are needed, and this need is exemplified by the Antarctic Peninsula region which encompasses rich marine, coastal, and terrestrial ecosystems but faces growing impacts and needs for taking action. In this study we applied the matrix method, an expert-based approach that employs a tabular matrix of ecosystem services and service providing units (SPUs) to elicit expert knowledge and rate the actual supply of key ecosystems services from the Antarctic Peninsula region. Further, we tested the applicability of this method on conventional definitions of SPUs and on objectively defined physico-chemical seascape units for a subset of the study region. Our results show high variations in the estimated supply of ecosystem services for the Antarctic Peninsula region, both with respect to the applied data models and in terms of the assessed services. While cultural and regulating services received highest supply estimates, provisioning services were regarded less relevant for the study region. Further, experts' supply estimates were much lower for the tested physico-chemical seascape units than for bathymetrically regionalized marine areas. The results suggest that a more explicit elaboration of linkages between ecosystem functions and processes and of the actual supply of ecosystem services is required in order to tap the full potential of such seascape data models in the context of qualitative, expert-based ecosystem service assessments.